2022
DOI: 10.1186/s13287-022-02722-5
|View full text |Cite
|
Sign up to set email alerts
|

Ricolinostat promotes the generation of megakaryocyte progenitors from human hematopoietic stem and progenitor cells

Abstract: Background Ex vivo production of induced megakaryocytes (MKs) and platelets from stem cells is an alternative approach for supplying transfusible platelets. However, it is difficult to generate large numbers of MKs and platelets from hematopoietic stem cells and progenitor cells (HSPCs). Methods To optimize the differentiation efficiency of megakaryocytic cells from HSPCs, we first employed a platelet factor 4 (PF4)-promoter reporter and high-thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…On the one hand, the limitations of the disease model itself lead to the distance gap from laboratory to clinic, and on the other hand, the safety and efficacy of ACY-1215 still need more clinical trials to prove. The latest researches also showed that ACY-1215 could improve the developmental competence of somatic cell nuclear transfer embryos ( Gao et al, 2022 ) and promote the generation of megakaryocyte progenitors ( Jiang et al, 2022 ).…”
Section: Future Perspectivementioning
confidence: 99%
“…On the one hand, the limitations of the disease model itself lead to the distance gap from laboratory to clinic, and on the other hand, the safety and efficacy of ACY-1215 still need more clinical trials to prove. The latest researches also showed that ACY-1215 could improve the developmental competence of somatic cell nuclear transfer embryos ( Gao et al, 2022 ) and promote the generation of megakaryocyte progenitors ( Jiang et al, 2022 ).…”
Section: Future Perspectivementioning
confidence: 99%
“…For co-culture experiments, CD34 + cells were labeled with 2 µM carboxyfluorescein succinimidyl ester (CFSE) dye (Thermo Fisher Scientific) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another study shows that inhibiting the secretion of IL-8 and its receptor, CXCR2 significantly enhances lineage commitment and proliferation of MKPs derived from cord blood HSPCs. This mechanism appears to be related to the upregulation of several key transcription factors involved in MK development following the inhibition of IL-8 [ 71 ]. With respect to platelet functionality, in vitro studies have shown that anti-IL-8 antibodies can stimulate platelet activation and enhance platelet coagulation activity in patients with heparin-induced thrombocytopenia.…”
Section: Mechanisms Of Interleukin Effects On Megakaryocyte Lineage C...mentioning
confidence: 99%